6 - African Media and the New Partnership for Africa’s Development (NEPAD) Agenda for Africa’s Emerging Democracies - Oluyinka Esan (Africa Media Review, 2004)
The paper discusses the peculiar location and roles assigned to media of communication in the democratic ideal. It makes a modest attempt to identify the share of the media in the creation of the problems commonly identified by the leaders in the continent. There is also a critique of the roles assigned to the media on the defined path to recovery. It begins with an examination of the model advanced by Habermas. This is a model based on the Libertarian principles upon which Western societies are founded. The paper identifies some of the contrasts between this Libertarian orientation and other theories of the press, and argues for what should be the ideal role of the media. To this end, it explores the location of the media in the aspirations of New Partnership for Africa’s Development (NEPAD).